Two Cycles of Carboplatin-based Adjuvant Chemotherapy for High-risk Clinical Stage I and Stage IM Non-seminomatous Germ Cell Tumours of the Testis: A HECOG Trial - Pectasides, D.; Skarlos, D.; Dimopoulos, A.-M.; Farmakis, D.; Pectasides, M.; Fountzilas, G.; Aravantinos, G. (Anticancer Research, 2003)
Background: We investigated the efficacy and safety of 2 cycles of adjuvant chemotherapy with carboplatin, etoposide and bleomycin (CEB 90) in patients with high-risk clinical stage I or stage IM non-seminomatous germ cell tumours (NSGCT). Patients and Methods: A total of 52 consecutive patients (22 patients with high-risk histological features [vascular invasion, presence of embryonal carcinoma, absence of yolk sac tumour] and 30 with tumour marker activity post-orchidectomy-stage IM) were entered into this prospective study. Chemotherapy consisted of carboplatin 400mg/m 2 or AUC 5 (day 1), etoposide 165mg/m2 (days 1-3) and bleomycin 30 mg (days 1, 8, 15). Chemotherapy was repeated every 3 weeks. Results: During a median follow-up of 112 months (range, 10 to 174 months), two patients with stage IM relapsed. These cases had a disseminated, marker-positive germ cell tumour (GCT), extensively involving both liver and lungs in the first case and para-aortic lymph nodes and lung in the second one; both patients died of the tumour after a number of salvage chemotherapy (including high-dose therapy) regimens. Fifty patients (96%) are alive and disease-free. Two cycles of CEB90 were well tolerated and the only side-effects were myelotoxicity and alopecia. Conclusion: Despite the general consensus that ciplatin-based chemotherapy is superior to carboplatin-containing regimens in testicular cancer, 2 cycles of CEB 90 may be an equally effective treatment option as adjuvant therapy for high-risk clinical stage I and IM patients.
Keywords: Adjuvant chemotherapy; Germ cell tumours; High-risk; Non-seminomas